Riwayat asupan energi dan protein yang kurang bukan faktor risiko stunting pada anak usia 6-23 bulan - Rahmaniah Rahmaniah; Emy Huriyati; Winda Irwanti (Alma Ata University Press, 2014)
ABSTRACTBackground: Stunting was a chronic nutrition problem that still be a concern in the developing nations include Indonesia. The direct cause of stunting was infectious disease and inadequate food intake such as energy and protein deficiency. In Indonesia in 2010, the prevalence of stunting was 35.7%, inYogyakarta as much as 22.5%, in Bantul District in 2012 was 18.08% and in Sedayu Subdistrict was 30.51%.Objectives: To know the history of energy and protein intake as the risk factors of stunting in children of 6-23 months.Methods: This was an observational study with case-control design. The population were children aged 6-23 months who lived in Sedayu Subdistrict, Bantul. The measurement energy and protein intake used a semi-quantitative food frequency questionnaire and determination of stunting used the WHO standard anthro 2005. Samples were selected by total sampling approachment. Data was analyzed by chi-square and logistic regression test.Results: The result of bivariate analysis showed that birth weight and maternal height had significant association with stunting (p<0.05). While energy and protein intake did not associated with stunting. However, there was a tendency that children with less energy and protein intake had higher risk of stunting. Multivariate analysis showed that maternal height was the dominant variable effect on the prevalence of stunting (OR=2.06).Conclusions: Low energy and protein intakes were not risk factors of stunting in children 6-23 months. Maternal height was dominant variable that influenced the stunting incidence.KEYWORDS: energy intake, protein intake, stunting, childABSTRAKLatar belakang: Stunting merupakan masalah gizi kronis yang masih menjadi perhatian di negara berkembang termasuk Indonesia. Penyebab langsung stunting adalah penyakit infeksi dan asupan makanan yang tidak memadai seperti kurang energi dan protein. Di Indonesia pada tahun 2010 prevalensi stunting sebanyak 35,7%, di Daerah Istimewa Yogyakarta sebanyak 22,5%, di Kabupaten Bantul tahun 2012 sebesar 18,08% dan Kecamatan Sedayu 30,51%.Tujuan: Untuk mengetahui riwayat asupan energi dan protein sebagai faktor risiko stunting pada anak usia 6-23 bulan.Metode: Jenis penelitian observasional dengan rancangan case-control. Populasinya seluruh anak usia 6-23 bulan yang ada di wilayah Kecamatan Sedayu Kabupaten Bantul. Pengukuran asupan energi dan protein dengan menggunakan semi-quantitative food frequency questionnaire dan penentuan stunting dengan menggunakan baku standar WHO anthro 2005. Cara pengambilan sampel adalah dengan total sampling. Analisis data menggunakan uji chi-square dan regresi logistik. Hasil: Berat bayi lahir dan tinggi badan ibu menunjukkan hubungan signifikan dengan kejadian stunting (p<0,05), sedangkan riwayat asupan energi dan protein tidak berhubungan dengan stunting (p>0,05). Secara multivariat, tinggi badan ibu merupakan variabel yang dominan berpengaruh terhadap stunting(OR=2,06).Kesimpulan: Asupan energi dan protein yang kurang bukan merupakan faktor risiko kejadian stunting pada anak usia 6-23 bulan. Tinggi badan ibu merupakan variabel yang dominan berpengaruh terhadap kejadian stunting.KATA KUNCI: asupan energi, asupan protein, stunting, anak